What's inside you? - Meredith, Susan; Chen, Kuo Kang; King, Colin; Wingham, Peter (London : Usborne ; Tulsa, Okla. : EDC Pub., 1991)
Examines the human body and its systems, including digestion, respiration, and circulation.
Includes index.
3.5
K-3.
K-3
Keywords: Human body -- Juvenile literature; Human physiology -- Juvenile literature; Human body; Human physiology; Human anatomy; Physiology